REMUNERATION JUSTICE IN ISLAMIC HIGHER EDUCATION: A STAKEHOLDER PERSPECTIVE - Azharsyah Ibrahim; Abdul Jalil Salam; Syahminan Syahminan; Ana Fitria (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
This study generally intends to analyze perception of remuneration justice from the perspectives of stakeholders in Indonesian Public Islamic Universities (PTKIN) that have acquired BLU status. Specifically, this study aims to measure the level of distributive and procedural justice on the implementation of remuneration at selected PTKIN. The respondents of this study are the beneficiaries and remuneration policy makers from 11 PTKIN that have implemented and paid the remuneration at the time of the study. Additional data are obtained from interviews with nine policy makers from the selected PTKIN. The data are analyzed using descriptive percentages method. The results show that in general the implementation of remuneration at the selected PTKIN in included within “fair” category as perceived by the stakeholders. Partially, respondents perceive procedural justice as "tend to be fair", while distributive justice is "fair". This shows that in terms of procedures, the selected PTKIN still have to work harder to fulfill a sense of justice, while from the distribution side it has given more sense of justice as perceived by most respondents.